American Realism: Historical Development and Major Contributors (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the rise and development of American realism, focusing on its major figures and their distinctive literary methods. It traces the origins of the movement, linking its growth to the social and economic transformations of the period, and outlines its defining traits. The works of leading realist authors are examined to demonstrate their roles in shaping and advancing the movement. Furthermore, the study considers how realism paved the way for subsequent literary trends, including naturalism and modernism.